Augmin complex activity finetunes dendrite morphology through non-centrosomal microtubule nucleation in vivo. - Zhang, Y.; Sung, H.H.; Ziegler, A.B.; Wu, Y.C.; Viais, R.; Sánchez-Huertas, C.; Kilo, L.; Agircan, F.G.; Cheng, Y.J.; Mouri, K.; Uemura, T.; Lüders, J.; et al. (Journal of Cell Science, 2024)
During development, neurons achieve a stereotyped neuron type-specific morphology, which relies on dynamic support by microtubules (MTs). An important player is the augmin complex (hereafter augmin), which binds to existing MT filaments and recruits the ?-tubulin ring complex (?-TuRC), to form branched MTs. In cultured neurons, augmin is important for neurite formation. However, little is known about the role of augmin during neurite formation in vivo. Here, we have revisited the role of mammalian augmin in culture and then turned towards the class four Drosophila dendritic arborization (c4da) neurons. We show that MT density is maintained through augmin in cooperation with the ?-TuRC in vivo. Mutant c4da neurons show a reduction of newly emerging higher-order dendritic branches and in turn also a reduced number of their characteristic space-filling higher-order branchlets. Taken together, our data reveal a cooperative function for augmin with the ?-TuRC in forming enough MTs needed for the appropriate differentiation of morphologically complex dendrites in vivo.